AB0194 Sparc is elevated in the affected skin of systemic sclerosis patients and induces the expression of fibrotic genes in dermal fibroblasts and macrophages. (12th June 2018) - García Pérez, S.; Malvar Fernández, B.; Bergin, M.; Johnson, T.; Marut, W.; Reedquist, K.A.; Radstake, T.R.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterised by inflammation, vascular injury and excessive fibrosis in multiple organs. SPARC is a matricellular glycoprotein that can bind to extracellular matrix (ECM) components, as well as cellular receptors and secreted growth factors. In doing so, SPARC regulates biological activities dependent upon cellular interactions with the ECM as well as processes dependent upon cell adhesion, including tissue remodelling, wound healing, angiogenesis and immune responses. Several studies have implicated SPARC in the pathology of SSc but the specific role of SPARC in fibrosis is still unknown. Objectives: The aim of this study was to analyse the potential role of SPARC as a regulator of fibrosis in SSc. Methods: Expression of SPARC in the skin of healthy donors (HD) and SSc patients was measured by immunohistochemistry. Peripheral blood-derived monocytes from HD and SSc patients were differentiated into macrophages with M-CSF (25 ng/ml). Dermal fibroblasts and M-CSF macrophages from both HD and SSc patients were stimulated with SPARC (0.1 and 1 µg/ml) for 6 hour and 24 hour. mRNA and protein expression of SPARC and other fibrosis-related genes were measured by qPCR and western blot. Results: We found increased expression of SPARC in the affected skin of SSc patients compared to HD. We also observed a higher expression of SPARC and ECM components (colagen(Col)−1 and fibronectin-1 (FN1) in dermal fibroblasts derived from SSc patients. SPARC stimulation induced mRNA expression of important fibrosis-related genes such as TGFB1, PDGFB, SERPINE1 and CTGF, and ECM components including COL1A1, COL3A1, COL4A1 and FN1 in dermal fibroblasts from SSc patients, but not healthy donors. In M-CSF macrophages from SSc patients, SPARC also up-regulated mRNA expression of TGFB1, PDGFB, STAB1, COL1A1 and FN1 . Conclusions: These results suggest that SPARC is an important pro-fibrotic mediator contributing to the pathology driving SSc. Therefore, SPARC could be a promising therapeutic target for reducing fibrosis in SSc. Disclosure of Interest: S. García Pérez: None declared, B. Malvar Fernández: None declared, M. Bergin Employee of: UCB, T. Johnson Employee of: UCB, W. Marut: None declared, K. A. Reedquist: None declared, T. R. Radstake: None declared